Genomics of worms, with an emphasis on Opisthorchis viverrini — opportunities for fundamental discovery and biomedical outcomes. Issue 4 (August 2017) - Gasser, Robin B.; Tan, Patrick; Teh, Bin Tean; Wongkham, Sopit; Young, Neil D.
Abstract: Neglected tropical diseases cause substantial morbidity and mortality in animals and people globally. Opisthorchiasis is one such disease, caused by the carcinogenic, Asian liver fluke, Opisthorchis viverrini. This hepatobiliary disease is known to be associated with malignant cancer (cholangiocarcinoma, CCA) and affects millions of people in Asia, including Thailand, Lao People's Democratic Republic (PDR) and Cambodia. No vaccine is available, and only one drug (praziquantel) is routinely employed against the parasite. Relatively little is known about the molecular biology of the fluke itself and the disease complex that it causes in humans. With the advent of high-throughput nucleic acid sequencing and bioinformatic technologies, it has now become possible to gain global insights into the molecular biology of parasites. The purpose of this minireview is (i) to discuss recent progress on the genomics of parasitic worms, with an emphasis on the draft genome and transcriptome of O. viverrini ; (ii) to use results from an integrated, global analysis of the genomic and transcriptomic data, to explain how we believe that this carcinogenic fluke establishes in the biliary system, how it feeds, survives and protects itself in such a hostile, microaerobic environment within the liver, and to propose how this parasite evades or modulates host attack; and (iii) to indicate some of the challenges, and, more importantly, the exciting opportunities that the 'omic resources for O. viverrini now provide for a plethora of fundamental and applied research areas. Looking ahead, we hope that this genomic resource stimulates vibrant and productive collaborations within a consortium context, focused on the effective control of opisthorchiasis. Graphical abstract: Highlights: Review progress on the genomics of parasitic worms, with an emphasis on O. viverrini Explain this carcinogenic fluke establishes, feeds and survives in the biliary system Propose how this parasite evades or modulates host attack O. viverrini genome should facilitate many fundamental and applied research areas.